Sejarah Kodifikasi Hadits - Ridwan, Agus Rifki; Zhistia Yuniarti; Muhammad Ridho (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Hadith is the second source of Islamic law after the Qur’an, so maintaining its authenticity is very important. Codification of hadith is the process of collecting, recording, and writing hadith systematically to avoid deviations and maintain the purity of the teachings of the Prophet Muhammad SAW. The purpose of writing this article is to study the history of codification of hadith, understand the background, process, and important stages in the effort to collect hadith of the Prophet Muhammad SAW. Hadith has an important position after the Qur’an, so codification is carried out to maintain authenticity and prevent the spread of false hadith. This study uses a library research method by analyzing primary and secondary sources related to the history of codification of hadith. The results of the study show that the codification of hadith occurred in several stages, during the time of the Prophet Muhammad SAW, hadith had not been written systematically and was only conveyed orally, its writing was limited to prevent mixing with the Qur’an. During the time of the Khulafaur Rasyidin, hadith began to be written in a limited manner. An important stage occurred during the time of Caliph Umar bin Abdul Aziz who ordered the official collection of hadith due to concerns about the loss of hadith due to the death of the narrators. This process was then continued by great scholars such as Imam Malik, Imam Al-Bukhari, and Imam Muslim, who compiled hadith books with a very strict selection method and full of caution so that their authenticity was maintained until the next generation.